Routledge handbook of the Arab Spring : rethinking democratization - Sadiki, Larbi (New York, : Routledge, 2015)
'The self-immolation of Mohammed Bouazizi in Tunisia in December 2010 heralded the arrival of the'Arab Spring,' a startling, yet not unprecedented, era of profound social and political upheaval. The meme of the Arab Spring is characterised by bottom-up change, or the lack thereof, and its effects are still unfurling today. The Routledge Handbook of the Arab Spring seeks to provide a departure point for ongoing discussion of a fluid phenomenon on a plethora of topics, including: - Contexts and contests of democratisation - The sweep of the Arab Spring - Egypt - Women and the Arab Spring - Agents of change and the technology of protest - Impact of the Arab Spring in the wider Middle East and further afield Collating a wide array of viewpoints, specialisms, biases, and degrees of proximity and distance from events that shook the Arab world to its core, the Handbook is written with the reader in mind, to provide students, practitioners, diplomats, policy-makers and lay readers with contextualization and knowledge, and to set the stage for further discussion of the Arab Spring'--
Preface: The Meme of the Arab Spring / Larbi Sadiki -- Part I. Introducing the Arab Spring: Reflections on Contexts and Contests of Democratization -- Part II. The'Travel' of Revolution: From Tunis to Sanaa -- Part III. Egypt in the Arab Spring: Islam, the State and the Military -- Part IV. Women's Voices in the Arab Spring -- Part V. Arab Spring: Breakdown of the Old Social Compact -- Part VI Uprisings: The Technology of Protest -- Part VII. The Arab Spring: The Wider Middle East -- Part VIII. The Arab Spring in a Global Context
Includes bibliographical references and index.
Keywords: Arab Spring, 2010-; Revolutions -- Arab countries -- History -- 21st century; Democratization -- Arab countires -- History -- 21st century